MENGEDUKASI KOMUNITAS ORANG MUDA TENTANG PENGELOLAAN MODAL UNTUK MENINGKATKAN KUALITAS DAN PRODUKSI KERAJINAN BERBASIS BUDAYA - Thomasita Bau Mau, Ignatia; Hendrikus Temai Lejap, Hedwigh; Dwi Ardhika Irianto, Eugenius; Maria Irayanti Seran, Adiutrix (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The Hamutuk Ita Bele Creative Community is a community-based organization engaged in preserving the culture of East Nusa Tenggara (NTT) through the production of local handicrafts. However, this community faces various challenges, especially in capital and financial management, which hinder the sustainability and development of its business. This Community Service (PKM) activity aims to increase the community's capacity in financial management and investment through five strategic stages, starting with basic financial management education. Initial implementation focused on cash recording, simple budget preparation, and collective fund management simulations. The results of the activity showed that the community did not yet have a structured financial system, limited capital, and difficulty in establishing partnerships. Further stages such as optimizing capital use, business diversification strategies, and access to financing have not been fully implemented due to the weak basic capacity. However, this activity has a positive impact in the form of increasing financial awareness of community members and practical learning for students in applying financial management concepts. With a gradual and collaborative approach, this program is expected to strengthen the sustainability of culture-based communities as a whole.